Comportamento germinativo das sementes de Vasconcellea quercifolia A. St.-Hil. (Caricaceae) - Pissatto, Marina (2015)
Vasconcellea quercifolia A. St.-Hil. (Caricaceae) is a native species of Rio Grande do Sul, popularly known as jaracatiá or mamãozinho do mato, and traditionally used in the preparation of sweets. Its fruits can be eaten raw or processed. Moreover, it is indicated for restoration of degraded areas and has economic potential, through the extraction of the enzyme papain, widely used in food and pharmaceutical industries. Despite its importance, there are few basic studies about the sexual reproduction of the species. This work aimed to study seed germination and seedling emergence. To do this, ripe fruits were collected from individuals growing naturally in the districts of Boca do Monte and Pains, Santa Maria, RS and the seeds were used for six germination experiments. We evaluated different substrates (sand, paper and vermiculite) and different forms of sowing (on or between); absence or presence of light (16 hour photoperiod), combined with constant temperatures (20, 25 and 30ºC) and alternating (20-30 ° C); influence of time of collecting fruits (February, March, April and May 2014); storing fruits in a refrigerator at 10 ± 1 °C for a week or not (fresh fruit), associated with pre-germination treatments in seeds; fruits stored in a refrigerator at 10 ± 1°C and subsequent storage or no seeds under the same conditions, which were submitted or not to pre-germination treatments; seed storage at different temperatures (10 or 25 ° C) and periods of time (30, 60, 90, 120 and 150 days). In seeds stored for 150 days was carried out tetrazolium test and germination test by testing on sowing and in vermiculite and pre-germination treatments. In the greenhouse, seedling emergence was studied after drying or no seeds at room temperature for 72 hours and the removal or not of mucilage that covers the seed coat of the same. Sowing on vermiculite was the most suitable for seed germination. The temperature of 25°C and 20-30°C associated with the presence of light (16 hour photoperiod) and total absence of light, respectively, have provided the best results of seed germination, which behaved as preferred positive photoblastic at constant temperatures and photoblastic neutral alternating temperature. Seed germination both at constant and absence of light, was practically nil. Seeds collected in February showed greater germination potential. Withdrawals of fresh fruit and seeds soaked in water for 24 hours and withdrawals of fruit stored in a refrigerator at 10 ± 1 ° C and treated with GA3 had the highest germination percentages. Storing seeds in refrigerator at 10 ± 1 ° C for a week did not favor the germination and storage of the same for different periods and temperatures caused reduced germination potential. However, after 150 days of storage, the tetrazolium test indicated that the seeds were viable, which was confirmed in the germination test conducted with seeds from the same batch and treated with GA3, which had high germination potential, demonstrating its orthodox behavior storage periods of up to five months. In the greenhouse, there were increases of seedling emergence rates in all treatments, beyond this present rapidly and uniformly.